2017
DOI: 10.1039/c7gc00160f
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Lewis and Brønsted acidic zeolites permit the continuous production of bio-renewable furanic ethers

Abstract: Bifunctional Sn- and Al-containing BEA zeolites, prepared by solid state incorporation, allow furanic ethers to be produced continuously at high (>80%) levels of selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…82 For a similar reaction (Figure 21), we also demonstrated that adding of a small amount of Brønsted acidity to a Sn-containing zeolite led to substantial improvements in stability of the transfer hydrogenation/etherification system. 91 In this case of bifunctional Sn,Al-, BMF selectivity was maintained above 70 % even after 2300 turnovers, whereas the selectivity in the Snonly system decreased to < 30 % after only 900 turnovers ( Figure 22).…”
Section: Poisoningmentioning
confidence: 86%
“…82 For a similar reaction (Figure 21), we also demonstrated that adding of a small amount of Brønsted acidity to a Sn-containing zeolite led to substantial improvements in stability of the transfer hydrogenation/etherification system. 91 In this case of bifunctional Sn,Al-, BMF selectivity was maintained above 70 % even after 2300 turnovers, whereas the selectivity in the Snonly system decreased to < 30 % after only 900 turnovers ( Figure 22).…”
Section: Poisoningmentioning
confidence: 86%
“…[86] Padovan et al suggested that bifunctionalB rønsted and Lewis acidic zeolites facilitatet he production of butoxy methyl furan via the etherification of furfural and 2-butanol. [164] They found that ab ifunctional H-BEA containing 2wt% Sn and 0.5 wt %A lg ave high ether selectivity (> 75 %) and exhibited excellent stability.B yc ontrast, monofunctional analogues or physicalm ixtures of the analoguesw ere less selective and stable. [164] Fang et al also found that Sn-MFI was effectivef or the etherification of BHMF with methanolt op roduce BMMF, achieving as electivity of 95 %.…”
Section: Role Of Cooperative Brønsted and Lewis Acidity In Selective mentioning
confidence: 99%
“…[164] They found that ab ifunctional H-BEA containing 2wt% Sn and 0.5 wt %A lg ave high ether selectivity (> 75 %) and exhibited excellent stability.B yc ontrast, monofunctional analogues or physicalm ixtures of the analoguesw ere less selective and stable. [164] Fang et al also found that Sn-MFI was effectivef or the etherification of BHMF with methanolt op roduce BMMF, achieving as electivity of 95 %. The authors found that BMMF formation increased with increasing Lewis acidityo ft he catalyst.…”
Section: Role Of Cooperative Brønsted and Lewis Acidity In Selective mentioning
confidence: 99%
See 2 more Smart Citations